An explosion composite copper-aluminum transition row of pure aluminum and red copper and a preparation method thereof
Patent Information
- Application Number
- CN202611296554.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-30
AI Technical Summary
现有铜铝过渡排主要存在如下技术缺陷:第一,连接可靠性差,传统焊接、螺栓连接方式易产生电化学腐蚀,接触电阻随时间增大,高温下易松动、发热甚至烧蚀;第二,界面结合强度不足,常规爆炸复合工艺未针对1060纯铝、C1100紫铜的材料特性进行优化,易出现界面脆化;第三,爆炸复合加工后板材端部残余应力大,后续裁切、打孔、折弯二次加工容易出现开裂;第四,爆炸冲击作用下板材容易出现板面翘曲、局部脱层缺陷,造成产品报废,服役过程中界面容易出现开裂,电阻逐步攀升,缩短设备使用寿命
[0029]1、本发明采用定向可控爆炸复合实现原子级一体式冶金结合,铜铝结合界面无分层、无裂纹、无氧化杂质夹层、无气泡空隙,规避螺栓连接、焊接带来的电化学腐蚀问题,不会出现接触电阻随服役时间增大的现象,高温工况下不会松动、发热烧蚀,提升输电系统运行可靠性。
Smart Images

Figure CN123017602A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrical connector technology, specifically to an explosive composite copper-aluminum transition busbar of pure aluminum and copper and its preparation method. Background Technology
[0002] Copper-aluminum transition busbars are core components connecting copper and aluminum busbars in power systems, new energy power generation, and rail transit, and their performance directly affects the reliability of the power transmission system. Existing copper-aluminum transition busbars suffer from the following technical defects: First, poor connection reliability; traditional welding and bolting methods are prone to electrochemical corrosion, increasing contact resistance over time, and are susceptible to loosening, overheating, and even ablation at high temperatures. Second, insufficient interface bonding strength; conventional explosive bonding processes are not optimized for the material properties of 1060 pure aluminum and C1100 copper, easily leading to interface embrittlement. Third, high residual stress at the ends of the sheet metal after explosive bonding processing, making subsequent cutting, drilling, and bending processes prone to cracking. Fourth, the explosive impact can cause sheet metal warping and localized delamination defects, resulting in product scrap; during service, interface cracking is likely to occur, resistance gradually increases, and equipment lifespan is shortened.
[0003] Existing technologies lack copper-aluminum transition busbar product structures that can simultaneously solve all of the above problems. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide an explosive composite copper-aluminum transition busbar of pure aluminum and copper and its preparation method, thereby solving the technical problems of electrochemical corrosion, increased contact resistance, interface embrittlement, secondary processing cracking, and board warping and delamination of traditional copper-aluminum transition busbars.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] This invention proposes an explosively composite copper-aluminum transition busbar of pure aluminum and copper, characterized by comprising a C1100 copper substrate and a 1060 pure aluminum cladding plate; the C1100 copper substrate and the 1060 pure aluminum cladding plate are vertically aligned and parallel to each other, and the copper-aluminum transition busbar is formed into an atomically integrated metallurgical bond structure through a directional controllable explosive composite process. The copper-aluminum bonding interface of the transition busbar is free of delamination, cracks, oxide impurities, and air bubbles; the 1060 pure aluminum cladding plate is integrally formed with a turret-type non-composite area and a stress-relieving positioning groove, the turret-type non-composite area being independently located at the end of the 1060 pure aluminum cladding plate; the stress-relieving positioning groove is formed on the bonding surface of the 1060 pure aluminum cladding plate; the copper-aluminum transition busbar undergoes stress-relief annealing modification treatment, with an interface bonding strength of not less than 200 MPa, an overall conductivity of not less than 95% IACS, and is able to withstand long-term high-current impact and alternating high and low temperature conditions, exhibiting excellent electrochemical corrosion resistance.
[0007] Preferably, the turret-type non-composite area is an integral structure extending from the end of a 1060 pure aluminum cladding plate, without any composite bonding with the C1100 copper substrate, and is a single pure aluminum homogeneous structure; the extension dimension of the turret-type non-composite area along the length direction of the 1060 pure aluminum cladding plate is 100mm to 150mm, and the plate thickness and flatness of the turret-type non-composite area are completely consistent with the main body of the 1060 pure aluminum cladding plate.
[0008] Preferably, the stress-relieving positioning groove is a rectangular strip groove structure that runs through the entire length of the 1060 pure aluminum cladding plate. The sidewalls of the groove are perpendicular to the surfaces to be bonded, and the bottom of the groove is flat and smooth. The stress-relieving positioning groove is precisely opened on the inner surface to be bonded between the 1060 pure aluminum cladding plate and the C1100 copper substrate. The groove depth is fixed at 1.5mm, and the horizontal distance between the groove and the inner edge of the C1100 copper substrate is fixed at 5mm. The groove is used to uniformly disperse the explosive impact stress and ensure the consistency of the interface bonding throughout the entire area.
[0009] Preferably, the C1100 copper substrate has a thickness of 6mm, the 1060 pure aluminum cladding has a thickness of 16mm, and the overall thickness of the copper-aluminum transition strip after the C1100 copper substrate and the 1060 pure aluminum cladding are composite formed is 22mm.
[0010] This invention proposes a method for preparing an explosively composite copper-aluminum transition busbar of pure aluminum and copper. The method employs a proprietary composite process involving pre-modification of the substrate structure, precise gap control during explosion, and low-temperature stress-relief annealing. This process avoids the defects of traditional copper-aluminum composites, such as interface embrittlement, stress concentration, and conductivity attenuation. The method includes the following steps:
[0011] S1. Pre-modification of substrate structure:
[0012] High-precision C1100 copper substrate and 1060 pure aluminum composite plate are cut separately. The end of the 1060 pure aluminum composite plate is processed into a regular turret-style non-composite area using plasma precision cutting process. The stress-relieving positioning groove is processed into the bonding surface of the 1060 pure aluminum composite plate using precision milling process. All processing burrs and stress gaps are removed to ensure that the substrate structure accuracy meets the standard.
[0013] S2. Ultra-clean surface finishing treatment:
[0014] The surfaces to be bonded by the C1100 copper substrate and the 1060 pure aluminum composite plate are cleaned in sequence by mechanical coarse grinding, fine polishing and organic solvent wiping. This completely removes the oxide layer, oil, dust and metal impurities from the board surface, prevents the formation of interfacial impurity interlayers, and ensures that the cleanliness of the board surface meets the requirements of metallurgical composite.
[0015] S3. Alignment gap adjustment:
[0016] The C1100 copper substrate is fixed horizontally, and the 1060 pure aluminum cladding is placed parallel above the C1100 copper substrate. The parallel composite gap between the two is adjusted and fixed.
[0017] S4, Point-to-Point Directional Controllable Explosive Composite:
[0018] The external explosion composite process with single-sided central detonation, combined with a double protection structure of upper surface isolation protection and lower surface flexible buffer, and constant adaptive detonation velocity control, enables the 1060 pure aluminum composite plate to impact the C1100 copper substrate at a uniform speed, parallel and close, to achieve uniform melting and metallurgical bonding throughout the entire area, without local overshoot or interface debonding.
[0019] S5. Low-temperature isothermal stress-relieving annealing treatment:
[0020] The exclusive annealing process of medium-low temperature constant temperature heat preservation and slow cooling in the furnace is adopted to accurately eliminate the instantaneous impact residual stress generated by the explosive bonding of C1100 copper substrate and 1060 pure aluminum composite plate, refine the metallographic structure of copper-aluminum interface, inhibit interface metal embrittlement, improve interface bonding stability and fatigue resistance, and avoid interface cracking and resistance increase problems during long-term use.
[0021] S6. Finished product finishing:
[0022] The annealed C1100 copper substrate and 1060 pure aluminum composite plate were leveled, cut, and chamfered to remove processing defects, resulting in the finished copper-aluminum transition plate.
[0023] Preferably, in step S1, the C1100 copper substrate is cut to a size of δ6mm×330mm×300mm, and the 1060 pure aluminum cladding is cut to a size of δ16mm×380mm×350mm; the processing length of the turret-type non-composite area is 100mm~150mm, the processing depth of the stress-relieving positioning groove is 1.5mm, and the processing distance between the stress-relieving positioning groove and the inner edge of the C1100 copper substrate is 5mm.
[0024] Preferably, in step S2, the surface roughness Ra of the surfaces to be bonded between the finished C1100 copper substrate and the 1060 pure aluminum cladding is ≤1.6μm, with no scratches, pits, or oxide spots; in step S3, the C1100 copper substrate and the 1060 pure aluminum cladding are kept in an absolutely parallel state throughout the process, and the uniform parallel composite gap between the two is strictly controlled to be 2mm~5mm, with no local gap deviation.
[0025] Preferably, in step S4, the detonation point is uniquely set at the geometric midpoint of the short side of the 1060 pure aluminum composite plate, and the offset of the detonation point from this geometric midpoint is ≤±15mm to ensure uniform diffusion of the explosion shock wave; a special protective oil is uniformly coated on the entire surface of the 1060 pure aluminum composite plate to form a full-coverage isolation and protective layer, preventing the high-temperature burning and oxidation corrosion of the 1060 pure aluminum composite plate surface by the explosive; a fiberboard is tightly laid on the entire lower surface of the C1100 copper substrate to form a full-coverage buffer pad layer to absorb the high-frequency impact energy of the explosion; the detonation velocity of the explosive is constantly controlled at 2500m / s~3500m / s to match the dissimilar metal composite characteristics of 1060 pure aluminum and C1100 copper.
[0026] Preferably, in step S5, the annealing process parameters are: heating temperature 300℃~350℃, constant temperature holding time 2h~4h, and after the holding time, the C1100 copper substrate and 1060 pure aluminum composite plate are slowly cooled to room temperature in the furnace.
[0027] Preferably, the isolation and protective layer completely covers the upper surface of the 1060 pure aluminum composite panel to prevent direct contact between the explosive and the 1060 pure aluminum composite panel and avoid ablation damage to the panel surface; the buffer pad layer completely adheres to the lower surface of the C1100 copper substrate to buffer the instantaneous impact stress of the explosion and prevent the C1100 copper substrate from deforming and cracking.
[0028] The beneficial effects of this invention are as follows:
[0029] 1. This invention uses directional controllable explosive composite to achieve atomic-level integrated metallurgical bonding. The copper-aluminum interface is free of delamination, cracks, oxide impurity layers, and air bubbles, avoiding the electrochemical corrosion problems caused by bolt connections and welding. It will not cause the phenomenon of contact resistance increasing with service time, and will not loosen or overheat and burn under high temperature conditions, thus improving the reliability of power transmission system operation.
[0030] 2. The present invention sets up a turret-type non-composite zone to eliminate residual stress at the end of the board, avoid cracking defects during secondary cutting, drilling, and bending, and improve the yield of finished products.
[0031] 3. The present invention is equipped with a stress-relieving positioning groove to achieve precise alignment of the explosive composite, uniformly release instantaneous impact stress, and eliminate defects such as board warping and local delamination.
[0032] 4. The product of this invention undergoes stress-relief annealing modification treatment to inhibit interface embrittlement. The interface bonding strength is not less than 200MPa, the conductivity is not less than 95%IACS, and it can withstand long-term high current impact and alternating high and low temperature conditions. It also has excellent electrochemical corrosion resistance. Attached Figure Description
[0033] Figure 1 This is a flowchart of the preparation method of the present invention. Detailed Implementation
[0034] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The scope of protection of the present invention is not limited to the following embodiments. Equivalent modifications and substitutions made by those skilled in the art based on the inventive concept all fall within the scope of protection defined by the claims of the present invention.
[0035] Example 1:
[0036] This embodiment discloses an explosive composite copper-aluminum transition plate consisting of a C1100 copper substrate and a 1060 pure aluminum cladding plate. The C1100 copper substrate and the 1060 pure aluminum cladding plate are arranged parallel to each other, forming an atomic-level integrated metallurgical bond through a directional controllable explosive composite process. The copper-aluminum interface is free from delamination, cracks, oxide impurity layers, and air bubbles.
[0037] The 1060 pure aluminum clad plate features an integrated molding process with a turret-style non-composite zone and stress-relieving positioning grooves. The turret-style non-composite zone is located at the end of the 1060 pure aluminum clad plate. This zone releases residual stress generated during the explosive bonding process at the plate's end, preventing cracking during subsequent cutting, drilling, and bending. The stress-relieving positioning grooves are located on the bonding surface of the 1060 pure aluminum clad plate. During the explosive bonding operation, they provide alignment and evenly distribute the instantaneous impact stress from the explosion, preventing warping, localized delamination, and other external and internal defects in the finished plate.
[0038] The finished copper-aluminum transition busbar undergoes a specialized stress-relief annealing modification treatment, achieving a measured interfacial bond strength of 220MPa~230MPa and an overall conductivity of 96.9%IACS~97.4%IACS, exceeding design standards. After high and low temperature alternating tests (-40℃~125℃, 500 cycles), the interface showed no cracking or delamination, with a resistance fluctuation value ≤1.2%. After 1000h of neutral salt spray testing, the interface showed no corrosion failure, demonstrating excellent weather resistance and electrical stability.
[0039] This embodiment adopts a metallurgical composite structure of C1100 copper substrate and 1060 pure aluminum cladding, combined with an integrated structural design of end turret-type non-composite area and stress-relieving positioning groove on the surface to be bonded, and combined with stress-relief annealing modification treatment, to achieve the structural performance of copper-aluminum transition row with high interface bonding strength, high conductivity and low residual stress, effectively solving the core problems of interface defects, easy cracking during processing and conductivity attenuation in traditional products.
[0040] Example 2:
[0041] This embodiment discloses an explosive composite copper-aluminum transition plate of pure aluminum and copper, including a C1100 copper substrate and a 1060 pure aluminum cladding plate. The C1100 copper substrate and the 1060 pure aluminum cladding plate are arranged in parallel and facing each other. An atomic-level integrated metallurgical bond is formed by a directional and controllable explosive composite process. There are no delamination, cracks, oxide impurity interlayers, or bubble voids at the copper-aluminum interface.
[0042] Both the C1100 copper substrate and the 1060 pure aluminum cladding plate are rectangular flat plates. The length and width dimensions of the 1060 pure aluminum cladding plate are larger than those of the C1100 copper substrate. During explosive composite assembly, the 1060 pure aluminum cladding plate extends beyond the C1100 copper substrate on all four sides. The rectangular flat plate has a long side and a short side. The long side refers to the side along the length of the rectangle, and the short side refers to the side along the width of the rectangle, providing a regular structural reference for targeted detonation.
[0043] The turret-style non-composite zone is an integral extension of the 1060 pure aluminum clad plate. This zone does not undergo metallurgical bonding with the C1100 copper substrate and remains a single, homogeneous pure aluminum structure. The turret-style non-composite zone extends 100mm to 150mm along the length of the 1060 pure aluminum clad plate, maintaining the same thickness and surface flatness as the main body. When the explosive composite shock wave reaches the end, residual stress concentrates within the turret-style non-composite zone. Subsequent cutting can remove this portion, preventing stress residue in the finished product's working area and thus preventing secondary processing cracking. The turret-style non-composite zone reduces the secondary processing cracking defect rate from over 12% to below 1%.
[0044] The stress-relief positioning groove is a rectangular strip that runs the entire length of the 1060 pure aluminum cladding plate. It is located on the inner side of the 1060 pure aluminum cladding plate facing the C1100 copper substrate, where the plates are to be bonded. The groove sidewalls are perpendicular to the bonding surface, and the bottom is flat and smooth. The groove depth is fixed at 1.5mm, and the horizontal distance between the groove and the inner edge of the C1100 copper substrate is fixed at 5mm. The groove is used to evenly disperse the explosive impact stress, ensuring consistent bonding across the entire interface. During the explosive impact, the stress-relief positioning groove can disperse concentrated local impact stress, reducing the risk of localized over-melting and embrittlement at the interface. Simultaneously, it serves as an alignment reference during assembly, ensuring the alignment accuracy of the two plates and reducing warping and delamination. The structure of the stress-relief positioning groove ensures uniform dispersion of explosive impact stress, reducing overall residual stress on the plate by more than 35%, controlling the warping of the finished plate to within 0.02mm, and eliminating localized delamination and over-melting embrittlement.
[0045] The isolation and protective layer completely covers the upper surface of the 1060 pure aluminum composite panel; during blasting operations, the isolation and protective layer separates the explosive from the panel body, preventing the high temperature burn and oxidation damage of the explosive to the surface of the 1060 pure aluminum composite panel.
[0046] The buffer pad is completely attached to the lower surface of the C1100 copper substrate; the high-frequency impact energy generated by the explosion is absorbed by the buffer pad, buffering the instantaneous impact stress and preventing the C1100 copper substrate from deforming and cracking.
[0047] In the finished copper-aluminum transition strip, the C1100 copper substrate is 6mm thick, the 1060 pure aluminum cladding is 16mm thick, and the total thickness after compositing is 22mm; the interface is atomic-level metallurgical bonded, without delamination, cracks, impurities, or interlayers.
[0048] The copper-aluminum transition busbar undergoes stress-relief annealing modification, resulting in an interfacial bonding strength of no less than 200MPa and an overall conductivity of no less than 95%IACS. It can withstand long-term high-current impacts and alternating high and low temperature conditions, and exhibits excellent resistance to electrochemical corrosion.
[0049] This embodiment precisely optimizes the stress state and bonding uniformity of the copper-aluminum composite interface by limiting the external dimensions, positional relationships, structural forms, and coordination methods of auxiliary protective structures of each core component. This achieves the goals of eliminating board warping, avoiding substrate deformation, reducing the probability of interface embrittlement, and improving product processing adaptability and finished product yield.
[0050] Example 3:
[0051] Figure 1 This is a flowchart of the preparation method of the present invention. Figure 1 As shown, this invention proposes a method for preparing an explosive composite copper-aluminum transition busbar of pure aluminum and copper, used to prepare the explosive composite copper-aluminum transition busbar of pure aluminum and copper disclosed in Example 2. It employs a proprietary composite process involving pre-modification of the substrate structure, precise gap control of the explosion, and low-temperature stress-relief annealing, avoiding the defects of traditional copper-aluminum composite interfaces such as embrittlement, stress concentration, and conductivity attenuation. The method includes the following steps:
[0052] S1. Pre-modification of substrate structure:
[0053] A rectangular flat C1100 copper substrate was selected and cut to a size of δ6mm×330mm×300mm; a rectangular flat 1060 pure aluminum cladding was selected and cut to a size of δ16mm×380mm×350mm.
[0054] Using plasma precision cutting, a turret-style non-composite area with a length of 100mm-150mm is processed at the end of the 1060 pure aluminum cladding plate. Using precision milling, stress-relieving positioning grooves are processed on the bonding surface of the 1060 pure aluminum cladding plate with a groove depth of 1.5mm and a horizontal distance of 5mm between the stress-relieving positioning grooves and the inner edge of the C1100 copper substrate. After processing, all burrs and stress gaps are removed to ensure the precision of the substrate.
[0055] S2. Ultra-clean surface finishing treatment:
[0056] Mechanical coarse grinding, fine polishing, and organic solvent wiping are performed sequentially to thoroughly clean the surfaces of the C1100 copper substrate and the 1060 pure aluminum composite plate to be bonded, removing oxide layers, oil stains, dust, and metallic impurities. After treatment, the surface roughness Ra is ≤1.6μm, and there are no scratches, pits, or oxide spots on the board surface. This prevents the formation of interfacial impurity interlayers and ensures that the cleanliness of the board surface meets the requirements for metallurgical composites and the cleanliness conditions for dissimilar metal metallurgical composites.
[0057] S3. Alignment gap adjustment:
[0058] The C1100 copper substrate is fixed horizontally, and the 1060 pure aluminum composite plate is placed parallel above the C1100 copper substrate. Ensure that the two plates are absolutely parallel, and control the parallel composite gap to 2mm-5mm, with no local gap deviation.
[0059] S4, Point-to-Point Directional Controllable Explosive Composite:
[0060] The external explosion composite process with single-sided central detonation is adopted. The detonation point is located at the geometric midpoint of the short side of the 1060 pure aluminum cladding plate, and the offset of the detonation point relative to the geometric midpoint is ≤±15mm. The short side of the 1060 pure aluminum cladding plate is the side of the rectangle in the width direction, and the long side is the side of the rectangle in the length direction. The shock wave propagates along the long side direction, and the shock wave spreads evenly.
[0061] A special protective oil is evenly applied to the entire surface of the 1060 pure aluminum composite panel to form a fully covered isolation and protective layer, preventing the surface of the 1060 pure aluminum composite panel from being burned or oxidized and corroded by the high temperature of the explosive. A fiberboard is tightly laid on the entire lower surface of the C1100 copper substrate to form a fully covered buffer pad layer, which is used to absorb the high-frequency impact energy of the explosion, buffer the instantaneous impact stress of the explosion, and prevent the C1100 copper substrate from deforming and cracking.
[0062] A special protective oil is applied to the upper surface of the 1060 pure aluminum cladding plate to form a fully covered isolation and protective layer; a fiberboard is laid on the lower surface of the C1100 copper substrate to form a fully covered buffer layer. The detonation velocity of the explosive is constantly controlled at 2500m / s-3500m / s; the explosion drives the 1060 pure aluminum cladding plate to impact the C1100 copper substrate at a uniform speed and in parallel, achieving uniform melting and metallurgical bonding over the entire area, without local overshoot or interface debonding.
[0063] S5. Low-temperature isothermal stress-relieving annealing treatment:
[0064] The exploded composite plate is sent into a heat treatment furnace and undergoes a special annealing process of medium-low temperature constant temperature holding and slow cooling with the furnace. Specifically, the heating temperature is 300℃-350℃, and the constant temperature holding time is 2h-4h. After the holding time is completed, the plate is slowly cooled to room temperature with the furnace.
[0065] The exclusive annealing process, which involves medium-low temperature constant temperature holding and slow cooling in the furnace, can eliminate residual stress caused by the explosion impact, refine the metallographic structure of the copper-aluminum interface, inhibit interface metal embrittlement, improve interface bonding stability and fatigue resistance by more than 40%, and prevent interface cracking and increased resistance during long-term service.
[0066] S6. Finished product finishing:
[0067] After annealing, the annealed C1100 copper substrate and 1060 pure aluminum composite plate are leveled, cut, and chamfered to remove processing defects, resulting in the finished copper-aluminum transition plate.
[0068] In this embodiment, 100 sets of samples were produced for trial production and sampling verification: the product interface bonding strength was stable at 218MPa~232MPa, and the conductivity was stable at 96.8%IACS~97.5%IACS; the temperature rise under rated operating conditions was only 28.3K, far below the national standard limit; the batch products showed excellent consistency and could be stably mass-produced industrially.
[0069] This embodiment employs a complete set of proprietary preparation processes, including substrate pre-modification, ultra-clean plate treatment, precise gap control, controlled-point explosive bonding, and low-temperature stress-relief annealing, combined with the unique product structure of this invention. This achieves defect-free metallurgical bonding of dissimilar metals, resulting in a high-strength, high-conductivity, low-stress, corrosion-resistant, and easily processed mass-producible finish.
[0070] The above is an exemplary description of the invention. Obviously, the specific implementation of the invention is not limited to the above-described manner. Any non-substantial improvement made using the inventive concept and technical solution of the invention, or the direct application of the inventive concept and technical solution to other situations without modification, is within the protection scope of the invention.
Claims
1. An explosive composite copper-aluminum transition busbar of pure aluminum and copper, characterized in that, The system comprises a C1100 copper substrate and a 1060 pure aluminum cladding plate. The C1100 copper substrate and the 1060 pure aluminum cladding plate are vertically aligned and parallel to each other, and are bonded together using a directional controllable explosive bonding process to form an atomically integrated metallurgical structure of copper-aluminum transition strips. The copper-aluminum interface of the transition strips is free of delamination, cracks, oxide impurities, and air bubbles. The 1060 pure aluminum cladding plate is integrally formed with a turret-type non-composite area and a stress-relieving positioning groove. The turret-type non-composite area is independently located at the end of the 1060 pure aluminum cladding plate. The stress-relieving positioning groove is located on the bonding surface of the 1060 pure aluminum cladding plate. The copper-aluminum transition strips undergo stress-relief annealing modification treatment, resulting in an interface bonding strength of not less than 200 MPa and an overall conductivity of not less than 95% IACS. It can withstand long-term high-current impact and alternating high and low temperature conditions, and exhibits excellent electrochemical corrosion resistance.
2. The explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 1, characterized in that, The turret-type non-composite area is an integral structure extending from the end of a 1060 pure aluminum composite plate, without any composite bonding with the C1100 copper substrate, and is a single pure aluminum homogeneous structure; the extension dimension of the turret-type non-composite area along the length direction of the 1060 pure aluminum composite plate is 100mm to 150mm, and the plate thickness and flatness of the turret-type non-composite area are completely consistent with the main body of the 1060 pure aluminum composite plate.
3. The explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 1, characterized in that, The stress-relieving positioning groove is a rectangular strip groove structure that runs through the entire length of the 1060 pure aluminum cladding plate. The sidewalls of the groove are perpendicular to the surfaces to be bonded, and the bottom of the groove is flat and smooth. The stress-relieving positioning groove is precisely opened on the inner surface to be bonded between the 1060 pure aluminum cladding plate and the C1100 copper substrate. The groove depth is fixed at 1.5mm, and the horizontal distance between the groove and the inner edge of the C1100 copper substrate is fixed at 5mm. The groove is used to evenly disperse the explosive impact stress and ensure the consistency of the interface bonding throughout the entire area.
4. The explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 1, characterized in that, The C1100 copper substrate has a thickness of 6mm, the 1060 pure aluminum cladding has a thickness of 16mm, and after the C1100 copper substrate and the 1060 pure aluminum cladding are composite formed, the overall thickness of the copper-aluminum transition strip is 22mm.
5. A method for preparing an explosive composite copper-aluminum transition busbar of pure aluminum and copper, characterized in that, The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper as described in any one of claims 1-4 comprises the following steps: S1. Pre-modification of substrate structure: High-precision C1100 copper substrate and 1060 pure aluminum composite plate are cut separately. The end of the 1060 pure aluminum composite plate is processed into a regular turret-style non-composite area using plasma precision cutting process. The stress-relieving positioning groove is processed into the bonding surface of the 1060 pure aluminum composite plate using precision milling process. All processing burrs and stress gaps are removed to ensure that the substrate structure accuracy meets the standard. S2. Ultra-clean surface finishing treatment: The surfaces to be bonded by the C1100 copper substrate and the 1060 pure aluminum composite plate are cleaned in sequence by mechanical coarse grinding, fine polishing and organic solvent wiping. This completely removes the oxide layer, oil, dust and metal impurities from the board surface, prevents the formation of interfacial impurity interlayers, and ensures that the cleanliness of the board surface meets the requirements of metallurgical composite. S3. Alignment gap adjustment: The C1100 copper substrate is fixed horizontally, and the 1060 pure aluminum cladding is placed parallel above the C1100 copper substrate. The parallel composite gap between the two is adjusted and fixed. S4, Point-to-Point Directional Controllable Explosive Composite: The external explosion composite process with single-sided central detonation, combined with a double protection structure of upper surface isolation protection and lower surface flexible buffer, and constant adaptive detonation velocity control, enables the 1060 pure aluminum composite plate to impact the C1100 copper substrate at a uniform speed, parallel and close, to achieve uniform melting and metallurgical bonding throughout the entire area, without local overshoot or interface debonding. S5. Low-temperature isothermal stress-relieving annealing treatment: The exclusive annealing process of medium-low temperature constant temperature heat preservation and slow cooling in the furnace is adopted to accurately eliminate the instantaneous impact residual stress generated by the explosive bonding of C1100 copper substrate and 1060 pure aluminum composite plate, refine the metallographic structure of copper-aluminum interface, inhibit interface metal embrittlement, improve interface bonding stability and fatigue resistance, and avoid interface cracking and resistance increase problems during long-term use. S6. Finished product finishing: The annealed C1100 copper substrate and 1060 pure aluminum composite plate were leveled, cut, and chamfered to remove processing defects, resulting in the finished copper-aluminum transition plate.
6. The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 5, characterized in that, In step S1, the C1100 copper substrate is cut to a size of δ6mm×330mm×300mm, and the 1060 pure aluminum cladding is cut to a size of δ16mm×380mm×350mm. The processing length of the turret-type non-composite area is 100mm~150mm, the processing depth of the stress-relieving positioning groove is 1.5mm, and the processing distance between the stress-relieving positioning groove and the inner edge of the C1100 copper substrate is 5mm.
7. The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 5, characterized in that, In step S2, the surface roughness Ra of the C1100 copper substrate and the 1060 pure aluminum cladding to be bonded after finishing is ≤1.6μm, with no scratches, pits, or oxide spots; in step S3, the C1100 copper substrate and the 1060 pure aluminum cladding are kept in an absolutely parallel state throughout the process, and the uniform parallel composite gap between the two is strictly controlled to be 2mm~5mm, with no local gap deviation.
8. The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 5, characterized in that, In step S4, the detonation point is uniquely set at the geometric midpoint of the short side of the 1060 pure aluminum cladding plate. The deviation of the detonation point from this geometric midpoint is ≤±15mm to ensure uniform diffusion of the blast shock wave. A special protective oil is evenly applied to the entire surface of the 1060 pure aluminum cladding plate to form a fully covered isolation and protective layer, preventing the high-temperature burning and oxidation corrosion of the 1060 pure aluminum cladding plate surface by the explosive. A fiberboard is tightly laid on the entire lower surface of the C1100 copper substrate to form a fully covered buffer pad layer to absorb the high-frequency impact energy of the explosion. The detonation velocity of the explosive is constantly controlled at 2500m / s~3500m / s to match the dissimilar metal composite characteristics of 1060 pure aluminum and C1100 copper.
9. The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 5, characterized in that, In step S5, the annealing process parameters are: heating temperature 300℃~350℃, constant temperature holding time 2h~4h, and after the holding time, the C1100 copper substrate and 1060 pure aluminum composite plate are slowly cooled to room temperature in the furnace.
10. The method for preparing the explosive composite copper-aluminum transition busbar of pure aluminum and copper according to claim 8, characterized in that, The isolation and protective layer completely covers the upper surface of the 1060 pure aluminum composite panel, which is used to isolate the explosive from direct contact with the 1060 pure aluminum composite panel and avoid burning damage to the panel surface; the buffer pad layer completely adheres to the lower surface of the C1100 copper substrate, which is used to buffer the instantaneous impact stress of the explosion and prevent the C1100 copper substrate from deforming and cracking.